Synergies of Devotion, Compassion, and Wisdom in Śāntideva for Buddhists and Christians - Makransky, John (Buddhist Christian studies, 2021)
This essay will focus on three kinds of practice that help structure Śāntideva's Bodhicaryāvatāra (BCA): (1) practices of faith and devotion, (2) practices for cultivating compassion, and (3) practices for cultivating the nondual wisdom of emptiness. We will explore how these three types of practice, as explained in the BCA text, function synergistically to inform and empower each other on the path of a bodhisattva. I will draw on selected verses of the BCA to illustrate this point, and then relate it to recent writings on Śāntideva by Christian theologians Perry Schmidt-Leukel and Mark Heim.